Performances on planet break - Raposo, O. (2020)
The “cyphers” are the privileged places of experiences exchange between the breakdancers, when young people of diferente crews and territories socialize through dance. From the filming of theses cyphers in a break dance event I problematize the performances of b-boys and b-girls, composed of a rich repertoire of movements, aesthetics, gestures and facial expressions. Experienced as liminal moments, these performance simulate sometimes symbolic confrontations of dramatized violences, sometimes feeling of belonging to the same urban culture, transforming a mass of dancers into a sense of community.